Phylogeography of the Endangered Franciscana Dolphin: Timing and Geological Setting of the Evolution of Populations - Nara, Luana; Cremer, Marta J.; Farro, Ana P. C.; Colosio, Adriana Castaldo; Barbosa, Lupércio A.; Bertozzi, Carolina P. [UNESP]; Secchi, Eduardo R.; Pagliani, Bruna; Costa-Urrutia, Paula; Gariboldi, Maria C.; Lazoski, Cristiano; Cunha, Haydée A. (Springer Nature, 2022)
Pontoporia blainvillei (Gervais & d’Orbigny, 1844), the franciscana dolphin, is the most endangered small cetacean in the Western South Atlantic. It is an endemic species with a coastal and estuarine distribution that has been divided into four Franciscana Management Areas (FMAs). We used the mitochondrial DNA control region to conduct a phylogeographic analysis to evaluate the population structure of the franciscana and the influence of paleoceanographic events on its biogeographic history. We found nine populations along the entire distribution (ΦST = 0.41, ΦCT = 0.38, p < 10–5), with estimated migration rates resulting in less than one female per generation. Populations from FMAIII and FMAIV in the south (including the Río de La Plata Estuary) showed higher long-term migration rates and effective population sizes than northern populations. The phylogeographic analysis supports the franciscana origin in the Río de La Plata Estuary, with further dispersal south and northwards. The first lineage split happened around 2.5 Ma, with lineage radiation throughout the Pleistocene until recent fragmentation events shaped current-day populations. We suggest that Pleistocene glaciations influenced the dispersion and population structure of the franciscana. Specifically, that the shift of the Brazil-Malvinas Confluence drove the dispersion northwards. Then, low sea-level periods caused either the isolation in estuarine refugia or local extinctions, followed by re-colonizations.
Keywords: Biogeography; Glaciation; Paleodrainages; Pleistocene; Pontoporia blainvillei; Population structure; Sea-level